Endoscopic treatment of post-laparoscopic sleeve gastrectomy leaks using a specifically designed metal stent - Tringali, Andrea; Bove, Vincenzo; Perri, Vincenzo; Landi, Rosario; Familiari, Pietro; Boškoski, Ivo; Costamagna, Guido (Endoscopy, 2017)
Background and study aim Leakage of the surgical suture is the main complication of laparoscopic sleeve gastrectomy (LSG) and is amenable to endoscopic therapy. The aim of this study was to evaluate the efficacy of a specifically designed self-expandable metal stent (SEMS) to seal the leakage.Patients and methods Over a 2-year period, patients referred for the treatment of post-LSG fistulas underwent placement of a fully covered esophagogastric SEMS with a specific design.Results A total of 10 patients were treated after a mean time of 50.9 days from the diagnosis of post-LSG leakage. A total of 11 SEMSs were placed. After stent removal, the leakage was seen to have healed in eight patients. Two patients who were treated with an SEMS with different mesh design, experienced stent migration, which required alternative endoscopic treatment such as the insertion of double-pigtail stents. After a mean follow-up period of 13.4 months, all patients were asymptomatic.Conclusions: Placement of a specifically designed SEMS for the treatment of post-LSG fistulas seems a promising first-line therapy according to this small series.